The trouble with honor eaudiobook Cabot sisters series, book 1. - London, Julia (The Cabot Sisters, 2014)
Passion and scandal collide in New York Times bestselling author Julia London's brand-new series about four sisters determined to rescue themselves from ruin . Desperate times call for daring measures as Honor Cabot, the eldest stepdaughter of the wealthy Earl of Beckington, awaits her family's ruin. Upon the earl's death she and her sisters stand to lose the luxury of their grand home-and their place on the pedestal of society-to their stepbrother and his social-climbing fiancEe. Forced to act quickly, Honor makes a devil's bargain with the only rogue in London who can seduce her stepbrother's fiancEe out of the Cabots' lives for good. An illegitimate son of a duke, George Easton was born of scandal and grows his fortune through dangerous risks. But now he and Honor are dabbling in a perilous dance of seduction that puts her reputation and his jaded heart on the line. And as unexpected desire threatens to change the rules of their secret game, the stakes may become too high even for a notorious gambler and a determined, free-spirited debutante to handle.